PENGARUH CASH RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSET PADA PT ASTRA INTERNASIONAL TBK PERIODE 2014 - 2023 - Ferdiyansah, Muhammad Rifki; Simangunsong, Ria Rosalia (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This research was created with the aim of knowing the effect of Cash Ratio and Debt to Asset Ratio on Return On Assets at PT Astra Internasional Tbk for the 2014 - 2023 period. This type of research is quantitative with a descriptive method with a sample size of 10 years. In processing the data in this study, SPSS version 27 was used. Based on the research results, it can be concluded that the T test on the independent variable Cash Ratio partially has no effect and is not significant on Return On Assets, because it has a Tcount value of -2.049 < Ttable 2.365 while the significance value is 0.080 > 0.05. So it can be concluded that the Cash Ratio has no effect and is not significant on Return On Assets. The independent variable Debt to Asset Ratio in the T Test shows a T value of -1.823 < T table 2.365 while the significance value is 0.162 > 0.05. So it can be concluded that partially the Debt to Asset Ratio has no effect and is not significant on Return On Assets. Based on the results of the F Test, all independent variables, namely Cash Ratio and Debt to Asset Ratio, simultaneously have no effect on Return On Assets, this is indicated by the Fcount value of 2,100 < Ftable 4.737 while the significance value is 0.193 > 0.05. So it can be concluded that the independent variables studied do not simultaneously influence the dependent variable.